Repair of huge thoracic defect combined with hernia after multimodality treatment of breast cancer - Evgeniy Topolnitskiy (Elsevier, 2021)
A case of the successful reconstruction of an extensive chest wall defect combined with a ventral hernia in a patient after multimodality treatment of breast cancer complicated by sternal and costal osteomyelitis is presented. To recover the chest mechanics, with emphasis on the supporting function, and to repair the hernial defect, customized reinforced “sandwich” TiNi rib endografts and knitted TiNi surgical mesh were used. A five-year follow-up indicated no recurrence of osteomyelitis or ventral hernia, and no failure/migration of the implants or instability of the thorax. Excellent clinical and functional outcomes were achieved pursuant to the Enneking score.